Analisis Kerentanan Sosial dan Kapasitas Adaptasi Masyarakat Terhadap Bencana Banjir di Kecamatan Sampara Kabupaten Konawe - Safril Kasim; La Ode Midi; La Ode Muhammad Erif; Surya Cipta Ramdhan Kete; Nurul Izzat Amaliah (PendIPA Journal of Science Education, 2026)
Floods are one of the most intense hydrometeorological disasters in Indonesia. As science and technology advances in flood hazard analysis, an in-depth analysis of social vulnerability and community adaptive capacity becomes crucial to ensure effective, measurable, and local-scale flood risk reduction, with communities as the primary actors. This study aims to determine the level of social vulnerability and community adaptive capacity to flooding in Sampara District, Konawe Regency. Using a mixed method, this study conducted a quantitative analysis to calculate the Social Vulnerability Index (SVI) using five main variables: population density, poverty ratio, sex ratio, disability ratio, and age group ratio. Meanwhile, a qualitative descriptive analysis was used to describe the implementation of the Hyogo Framework in enhancing disaster adaptive capacity, consisting of five capacity elements: institutional capacity, social capacity, economic capacity, and knowledge capacity and disaster literacy. The results of this study indicate that the SVI Index falls into the low category, although the sex ratio and age group ratio variables fall into the high category. Meanwhile, community adaptive capacity is generally low, with the main strengths being social networks, mutual cooperation, and social trust. The implications of this research finding are the need for inclusive policies to reduce vulnerability of communities, as well as to increase institutional, economic, physical, and disaster literacy capacity.